Fenomena Public Figur yang Mengikuti Upacara Melukat dalam Perspektif Islam - yumna, atikah nuraini (Universitas Islam Syekh-Yusuf, 2022)
This paper aims to find out the Islamic perspective in viewing the phenomenon of public figures who perform melukat ceremonies. The research method used in this study is qualitative with a descriptive approach, data collection techniques through literature studies. The results obtained in this study are that carrying out ceremonies that are not Islamic teachings should be avoided because they cause more harm. One of the ceremonies that many public figures participate in is the melukat ceremony with the aim of self-cleaning and calming the soul. In Islam there are many solutions that can deal with life and health problems. Religious therapy can be done by having faith in Allah SWT, worshiping by means of prayer, fasting reading the Qur'an, dhikr, and prayer